Changes in Atmospheric Dynamics Over Dansgaard‐Oeschger Climate Oscillations Around 40 ka and Their Impact on Europe - Stadelmaier, Kim H.; Ludwig, Patrick; Pinto, Joaquim G.; Újvári, Gábor (John Wiley and Sons, 2024)
Dansgaard-Oeschger (D-O) climate variability during the last glaciation was first evidenced in ice cores and marine sediments, and is also recorded in various terrestrial paleoclimate archives in Europe. The relative synchronicity across Greenland, the North Atlantic and Europe implies a tight and fast coupling between those regions, most probably effectuated by an atmospheric transmission mechanism. In this study, we investigated the atmospheric changes during Greenland interstadial (GI) and stadial (GS) phases based on regional climate model simulations using two specific periods, GI-10 and GS-9 both around 40 ka, as boundary conditions. Our simulations accurately capture the changes in temperature and precipitation as reconstructed by the available proxy data. Moreover, the simulations depict an intensified and southward shifted eddy-driven jet during the stadial period. Ultimately, this affects the near-surface circulation toward more southwesterly and cyclonic flow in western Europe during the stadial period, explaining much of the seasonal climate variability recorded by the proxy data, including oxygen isotopes, at the considered proxy sites.